Zarządzanie jakością w przedsiębiorstwie usługowym: Quality management in the enterprises service - Toruński, Janusz (Management and Administration Journal, 2021)
Service companies operate in an increasingly complex market environment. Increasing competition, continued placing on the market of new services, increasing prosperity and increasing knowledge and, therefore, consumer expectations make it necessary to adjust the quality of service to these conditions. You can also see the quality of leveling the bids of competitors. The article attempts to present conditions in the enterprise quality management services.